"When love does not bear a fruit": Patterns and prevalence of sexual difficulties in infertile men and women as predictors of emotional distress - Ansha Patel; P. S. V. N. Sharma; Pratap Kumar (Wolters Kluwer Medknow Publications, 2021)
Background: Self-identity, sexuality, and subfertility have multidirectional effects on each other. Subfertility is known to alter sexual esteem, threaten identity, body image, sexual attractivness, coital pleasure, and sexual satisfaction. Objective: This study aimed to evaluate sexual difficulties as predictors of infertility-specific stress in patients undergoing fertility treatments and to assess the profile of sexual dysfunctions in participants. Study Setting and Design: This cross-sectional study was conducted in a tertiary hospital setup of a medical college. Methods: Three hundred married men and women diagnosed with infertility participated. The psychological evaluation test, international classification of diseases (10th, CDDG), female sexual functioning index, and international index of erectile functioning were used as measures. Statistical Analysis: Data were analyzed using SPSS (version 15, Chicago, USA). Chi-square test was used for univariate analysis between stress and presence of sexual dysfunctions in men and women. Medians, quartile, and cutoff scores were used to profile the sexual issues in participants. Results: Prevalence of sexual dysfunctions since marriage was higher in women (75%) than men (60%). Ninety-two percent of women and 86% of men experienced emergence of sexual difficulties after the couple started treatments. Conclusions: Sexual dysfunctions appear to be a consistent psychosocial concern for those awaiting conception. These appear to worsen during the treatments. Our findings suggest the need to sensitively approach and explore sexual anamnesis with the couple before recourse to medically assisted reproductive treatments. Psychological interventions for sexual issues in distressed patients before, during, and after treatments such as controlled ovarian hyperstimulation, intrauterine insemination, in vitro fertilization, and intracytoplasmic sperm injection are most needed.